Determination of Nitrogen, Phosphorus and Potassium in Soil and Plant Due to Husbandry Farming in Parit Rasipan Drainage System - Miswan, Muhammad Safwan; Hamdan, Rafidah; Azman, Muhammad Hafiq Afifi; Ab. Aziz, Nur Adila; Siddiqui, Zuhaib (International Journal of Sustainable Construction Engineering and Technology, 2023)
Nutrient flow into waterways and soils has rapidly causing eutrophication, which causes ecological instability, dissolved oxygen (DO) depletion, extinction of aquatic species, and perhaps public health risks. Therefore, this study focuses on the determination of nitrogen, phosphorus, and potassium (NPK) in soil and plants in the Parit Rasipan drainage system due to the livestock farming area. The water quality of the drainage system is being monitored. Soil and plant at the study area have been collected by grid sampling method at 4 sampling points on wet and dry seasons for N determination using APHA 4500 NORG-B and PK using US EPA 6010B (ICP OES) methods, respectively. In addition, water quality has been monitored in situ for pH, DO, and temperature by a HI 98192 HANNA multiparameter instrument, while water samples were collected and analyzed for selected parameters including total nitrogen (TN), total phosphorus (TP) using the HACH DR6000 Spectrophotometer and potassium (K) by atomic absorption spectroscopy (AAS). The results of this study show that the concentrations of TN (3380–6290 mg/kg), TP (450-820 mg / kg) and K (381–931 mg/kg) in the soil are classified as moderate to very high. Due to the high concentration, TN (5270–6870 mg/kg), TP (262-769 mg / kg) and K (10200–16200 mg/kg) concentrations in plants are also high. For water quality monitoring, the data shows (pH 6.1-6.4), (DO 0.8–1.1 mg/L), and (temperature 26.6-29.2?C) both in wet and dry seasons. The concentrations of TN, TP and K (average ± s.d) concentrations in water during the wet season are (TN 43 ± 1mg/L), (TP 0.4 ± 1mg/L) and (K 3.9 ± 0.2mg/L) while during the dry season are (TN 49 ± 1mg/L), (TP 0.7 ± 1mg/L) and (K 4.2 ± 0.2mg/L). In conclusion, from the analysis of the results, the Parit Rasipan drainage system has a high level of NPK in both the wet and dry seasons due to the livestock activities in the area.